2024
DOI: 10.1007/s11214-024-01041-w
|View full text |Cite
|
Sign up to set email alerts
|

Essentials of Strong Gravitational Lensing

Prasenjit Saha,
Dominique Sluse,
Jenny Wagner
et al.

Abstract: Of order one in $10^{3}$ 10 3 quasars and high-redshift galaxies appears in the sky as multiple images as a result of gravitational lensing by unrelated galaxies and clusters that happen to be in the foreground. While the basic phenomenon is a straightforward consequence of general relativity, there are many non-obvious consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Hence, the effect of lensing should also enhance the observed TDE fluxes, which will bring more highz (Pop III) TDEs into view. While it has been shown that the chance of having a high-z galaxy lensed is roughly ∼10 −3 (Saha et al 2024), the probability of having lensed transients is yet to be studied in detail.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Hence, the effect of lensing should also enhance the observed TDE fluxes, which will bring more highz (Pop III) TDEs into view. While it has been shown that the chance of having a high-z galaxy lensed is roughly ∼10 −3 (Saha et al 2024), the probability of having lensed transients is yet to be studied in detail.…”
Section: Summary and Discussionmentioning
confidence: 99%